Systems approach towards surface water distribution in Kruger National Park, South Africa - Smit, Izak (Pachyderm, 2013)
There was concerted effort, especially between the 1960s and 1990s, to increase the distribution of surface water in Kruger National Park (KNP). As a consequence, most of the park was within easy walking distance of a permanent water source for large, mobile herbivores during the peak of the water-for-game programme. This situation was unnatural and led to various unintended ecological effects. In reaction to this and in response to changing conservation and management paradigms, the water provision policy was revised in 1997. Since the policy change, about two-thirds of the more than 300 boreholes have been closed and many catchment dams have been breached in an ongoing process. This new approach towards water provision has a strong spatial focus and aims to recreate and mimic a more natural mosaic of spatio-temporal variability in surface water availability. KNP managers hope that the change in water provision will induce spatial and temporal variation in how elephants utilize landscapes, which is a key objective of the current KNP Elephant Management Plan. Although it seems unlikely that the reduced availability of water has had any numerical effects on the elephant population thus far, it did induce some spatial changes: elephants are now even more strongly attracted to the large river systems than before. More research is needed to ascertain whether surface water manipulation in KNP, where water is naturally relatively widely distributed, is effective in creating spatio-temporal refugia for biodiversity that are sensitive towards elephant impacts. L’on a vu des efforts concertés, surtout entre les années 1960 et 1990, d’augmenter la distribution de l’eau de surface dans le Parc National Kruger (PNK). En conséquence, la plus grande partie du parc se trouvait à une courte distance de marche d’une source d’eau permanente pour les grands herbivores mobiles lors du pic du programme de l’eau-pour-la-faune. Cette situation était anormale et a conduit à divers effets écologiques inattendus. En réaction à cela et en réponse à l’évolution des paradigmes de conservation et de gestion, la politique d’approvisionnement en eau a été révisée en 1997. Depuis le changement de politique, environ deux tiers des plus de 300 forages ont été fermés et de nombreux barrages de captage percés dans un processus continu. Cette nouvelle approche d’approvisionnement en eau a une forte concentration spatiale et vise à recréer et à imiter une mosaïque plus naturelle de variabilité spatio-temporelle de la disponibilité en eau de surface. Les gestionnaires du PNK espèrent que la variation de l’approvisionnement en eau va induire des variations spatiales et temporelles dans la façon dont les éléphants utilisent les paysages, ce qui est un objectif clé du plan actuel de gestion des éléphants du PNK. Bien qu’il semble peu probable que la disponibilité réduite de l’eau ait eu des effets numériques sur la population des éléphants à ce jour, elle a induit quelques changements spatiaux: les éléphants sont encore plus fortement attirés par les grands systèmes fluviaux qu’auparavant. Il faut plus de recherche pour déterminer si la manipulation des eaux de surface dans le PNK où l’eau est assez largement distribué naturellement, est efficace dans la création de refuges spatio-temporels de la biodiversité sensibles aux impacts des éléphants.